Efeitos de reservatórios em cascata sobre a biologia reprodutiva de um piscívoro neotropical - Silva, Pedro Rogério Leandro da (2010)
Information about the events of life cycle of fish species are the most used for management measures, thus, this study seeks to determine under what conditions Pimelodus britskii is reproducing in the reservoir cascade of the Iguaçu river. Thus, the hypothesis being tested here is: the reproductive biology of this species is not influenced by the sequential of reservoirs? Data were collected between 2004 and 2008 (sampled quarterly) in five sequential reservoirs of the Iguaçu river (Foz do Areia, Segredo, Salto Santiago, Salto Osorio and Salto Caxias) through in the environmental studies of companies Tractebel Energia through the project Ichthyological studies and water quality monitoring of Salto Santiago and Salto Osório reservoirs - Iguaçu river/PR (Salto Santiago, Salto Osorio) and Companhia Paranaense de Energia through the project Biological Analysis of fishes (Foz do Areia, Segredo and Caxias). Samples were collected with gillnets and trammel nets (witches) that were exposed for 24 hours in three strata (margin, surface and bottom). To indentify significant differences between the reservoirs, the mean and median values of catch per unit effort (CPUE), sex ratio (χ²), gonad condition (ΔK), gonadosomatic relationship (RGS) and index of reproductive activity (IRA) were tested by main effect variance analysis, being controlled the temporal variability through blocks. The results of CPUE showed higher catch in Salto Santiago and Caxias reservoirs (23.5 and 21.2 individuals 1.000m²*net*day-¹, respectively), without significant difference between the reservoirs. General sex ratio showed no significant difference (χ²=1.70; 1:1), but significant differences were recorded between Segredo and Salto Santiago reservoirs. The length-weight relationship fitted the model Wc=0.0043LS3, 2106 (R2=0.9813) indicating that the values of ΔK increases with growth (allometric positive). The average values for gonad condition factor suggested greater weight/length relationship for the individuals of Salto Osorio (0.000251) and lower at Caxias (0.00005), indicating a significant difference between Caxias and the other reservoirs, except Segredo. The RGS for female in reproduction showed no significant difference between the reservoirs. The IRA was classified as incipient to intense between Foz do Areia (3.97) and Salto Osorio (11.02), indicating differences between the medians, however, showed no reservoirs which differ among themselves. Thus, the reproductive biology of P. britskii along the gradient of the cascade is not being affected due to environmental conditions of the Salto Santiago reservoir, however, after this place the results indicate trend of influence.